AKIBAT HUKUM PERKAWINAN CAMPURAN TERHADAP KEDUDUKAN HARTA KEKAYAAN BERDASARKAN HUKUM PERDATA INTERNASIONAL - Aprilianti, Ajeng; Putri, Revanissa Dwi Hardianti; Kania, Meisya Adinda Putri; Rahma, Santi; S.T., S.H., M.KN., M.H., Dr. Happy Yulia Anggraeni, (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
Mixed marriages between Indonesian citizens (WNI) and foreign citizens (WNA) in Indonesia are an increasing phenomenon due to globalization. However, these marriages present complex legal challenges, especially in the regulation of property and children's citizenship status. Based on Law Number 1 Year 1974 on Marriage, as well as other regulations such as the Basic Agrarian Law and Law Number 12 Year 2006 on Citizenship, various issues arise due to differences in legal principles between different jurisdictions. Property in mixed marriages, including joint property, inherited property, and inheritance, is often a source of legal conflict, especially when it involves immovable assets such as land.  On the other hand, the citizenship status of children from mixed marriages is regulated through temporary dual citizenship, which must be decided when the child reaches the age of 18. Although regulations have been updated to provide better legal protection, legal differences between countries still create potential disputes. Therefore, this research highlights the importance of prenuptial agreements, legal consultations, and alignment of national and international legal policies to address issues in mixed marriages fairly and effectively.